Characteristics of the genetic structure at the beta- and kappa-casein locus in the studied dairy breeds of cattle - Marzanov N.S.; Devrishov D.A.; Marzanova S.N.; Bukarov N.G.; Libet I.S. (E3S Web of Conferences, 2024)
In total, the research involved 148 heifers and cows of two breeds: Simmental and Ayrshire. Whole blood samples were obtained from three regions: Tambov (Simmental), Tula and Vladimir (Ayrshire) regions. Two breeds were analyzed for two milk protein loci: beta-casein (CSN2) and kappa-casein (CSN3). The results of a comparative assessment of the frequency of occurrence of alleles and genotypes at the beta-casein (CSN2) and kappa-casein (CSN3) loci in the two studied breeds are presented. A narrowing of the allelotype was noted in cows of the Ayrshire breed. Genogeographic analysis showed that polymorphism and the formation of the allelotype of the studied populations are influenced by breed, level of selection work, direction of productivity and possibly the external environment. In heifers and cows of the studied breeds, the total occurrence of “bad” CSN2A1 and CSN2B alleles at the beta-casein locus was higher than CSN2A2. Both breeds completely lacked the CSN2A3 allele, and the Ayrshires had the even worse CSN2A1/B genotype. The reason for this situation is the lack of demand and selection focus in working with breeds based on the beta- and kappa-casein locus. An imbalance of genetic balance was noted at the beta-casein locus in the Ayrshire population of the Tula region (χ2=4.890311; df=1; Р<0.05), at the kappa-casein locus in Simmental heifers (χ2=11.0435; df=1; Р<0.001) and a tendency to disturb the genetic balance was noted in Ayrshire cows of the Tula region (χ2=3.816924; df=1; Р~0.05). In the studied breeds, mutant CD18A, SLC35A3G, FANCIBY alleles causing hereditary diseases in dairy cattle were not identified.